BENTUK, FUNGSI, MAKNA DAN WARNA TOPENG REOG PADA KESENIAN REOG SINGO LADOYO DI KENAGARIAN TARATAK TINGGI KECAMATAN TIMPEH KABUPATEN DHARMASRAYA - Novia Sari Mulya; Ernis Ernis; Wisdiarman Wisdiarman (Universitas Negeri Padang, 2020)
Singoladoyo’s reog mask is often displayed in weddings, circumcisions, and other entertainment events. Many people do not know about the form, functions, meaning, and color, especially the Minangkabau tribe in Taratak Tinggi. The purpose of this study was to examine the mask shape, function, meaning, and color of the reog mask. The method used is qualitative with a descriptive approach. The result of this study are three types of masks, namely: Singo Barong in the form of a tiger head, ganong mask in the shape of a scary human face with a long nose, and bulging eyes, mask shaped sewandono klono face that resembles a god. The function of each mask is purely as an art of entertainment. While the meaning is taken from the history of the kingdom of Wengker in Ponorogo. Reog mask has a variety of colors, namely tiger stripes: (yellow, black, white), red and green.